Social Frailty in Late Adulthood: Social Cognitive and Psychological Well-Being Correlates. (3rd October 2022) - Henry, Julie D; Coundouris, Sarah P; Mead, Jessica; Thompson, Brielle; Hubbard, Ruth E; Grainger, Sarah A
Abstract: Objectives: Social frailty poses a major threat to successful aging, but its social cognitive and psychological well-being correlates remain poorly understood. This cross-sectional study provides initial insights into whether social cognitive difficulties in older age are associated with social frailty, as well as how social frailty is linked to psychological characteristics known to be important for health and well-being. Method: Ninety community-dwelling older adults completed measures of social frailty and social cognition (social perception, theory of mind, affective empathy, and informant-rated social behavior) as well as measures of psychological function known to be important for health and well-being, both positively (resilience and life satisfaction) and negatively (demoralization, social anxiety, and apathy). Measures of cognitive frailty, physical frailty, and depression were also administered to test the specificity of any observed relationships with social frailty. Results: Both affective empathy and social behavior were predictive of increased social frailty, but social behavior emerged as the only unique predictor after controlling for covariates. Social frailty also predicted unique variance in all five measures of psychological well-being, and for three of these measures (demoralization, resilience, and life satisfaction), the effects remained significant even after adjusting for covariates. Discussion: Findings are discussed in relation to models of socioemotional aging and frailty. Potential mechanisms linking social behavior to social capital in older age are identified, as well as how loss of social resources might both directly and indirectly impact well-being.